Associations of alcohol intake with subclinical carotid atherosclerosis in 22,000 Chinese adults - Zhou, T; Im, PK; Hariri, P; Du, H; Guo, Y; Lin, K; Yang, L; Yu, C; Chen, Y; Sohoni, R; Avery, D; Guan, M; et al. (Elsevier, 2023)
Background and aims We investigated the causal relevance of alcohol intake with measures of carotid artery thickness and atherosclerosis in Chinese adults.